Aplicación de perlas de quitosano modificado con hierro para adsorción de mercurio en soluciones acuosas. - Romero Suárez, Cristhian Andrés (2017)
The chitosan is a biopolymer that is obtained from the shells of the shrimp by means of a chemical or enzymatic treatment, which has application in processes of adsorption of metallic ions; among those is mercury, which is a toxic heavy metal and detrimental to health. In addition, the chitosan is a low-cost biosorbente, efficient and friendly with the environment that is used in pharmaceutical industries, food, textile, as well as in the preparation of cosmetics, the agriculture, etc. Because of the properties that the chitosan possesses, it is possible to convert it to diverse forms (beads, membranes, nanoparticles, gels) and modify it to increase his capacity to adsorb metallicions. According to what was expressed, the aim of this investigation is adsorb mercury using beads of chitosan modified with iron [ChiFer (III)], to evaluate its capacity and speed of adsorption. It used ChiFer (III) dried to the air and ChiFer (III) freeze-dried, werevied provided by the Group on Techniques for Separating and Treating Industrial Waste (SETRI) of the Polytechnical University of Catalonia. To make the study of adsorption, firstly the researchers proceeded to make a study of pH, with solutions of Hg (50 ppm) to pH 2, 3, 4, 5 and 6, during 48 hours to 200 rpm with 20 mg of ChiFer (III); to determine the conditions in which it produced the greater percentage of adsorption. It is known that at acidic pH the protonation of the chelating groups of the adsorbent is produced, and alcaline pH precipitates metals. With the optimum pH obtained we proceeded to make the experimentations for the construction of the curves of isotherms and kinetics of adsorption. In the literature several mathematical models that use were found are to adjust the experimental data of isotherms of equilibrium and likewise to describe the kinetics of adsorption. In the present study, the experimental data of the isotherms of adsorption were adjusted to the models of Langmuir and Freundlich. In the case of the data of adsorption for kinetics adjusted to the mathematical models of pseudo first and pseudo second order, with the purpose to know the dominant mechanism of the system. The capacities of adsorption for ChiFer (III) dried to the air and freeze-dried were high compared with other synthesized adsorbents with chitosan, being these 311 mg Hg g-1 ChiFer (III) dried to the air and 399 mg Hg g-1 ChiFer (III) freeze-dried. In addition, the data of adsorption adjusted to the kinetical model of pseudo second order, the same that allowed to know the constant of speed for each adsorbent material, being 0,00009 g mg-1 min-1 for ChiFer (III) dried to the air and 0,0000735 g mg-1 min-1 for ChiFer (III) freeze-dried. In this work it was demonstrated that the ChiFer (III) dried to the air and ChiFer (III) freeze-dried are material efficient for the adsorption of Hg, with capacities of high adsorption. The ChiFer (III) dried to the air was adjusted to the model of Langmuir and the ChiFer (III) freeze-dried was adjusted to the model of Freundlich, letting us know that the adsorption of Hg is conducted in monolayer and in multilayer respectively.